Analytics, innovation, and organizational adaptation. Issue 1 (2nd January 2017) - George, Gerard; Lin, Yimin
Abstract: With the advent of big data, organizations are integrating powerful computing tools into their organizational processes to drive efficiencies and improve service delivery. Yet, at the heart of this conversation lies the role of analytics and big data in innovation within and across organizations. In this article, we provide a stylistic model of the role of analytics in innovation and call for further research on the underlying processes, contingencies, and outcomes.